The Muslim Feminist Movement of the Indonesian Women Ulema Congress (KUPI) on Women's Issues in Indonesia - Asy'ari, Hasyim; Zuhriyah, Luluk Fikri (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
KUPI Muslim feminists are born from religious leaders who are sensitive to women's issues. They examine religious texts from a gender perspective, balancing the roles between patriarchal traditions and equality education, on the basis that Islam teaches inclusive justice for all humans. This paper uses a qualitative method with a social approach through Coleman's rational choice theory as an analytical tool on the data findings. The findings in this paper show that the KUPI Muslim feminist movement is based on rational choices constructed through Islamic religious values sourced from sacred texts with a scientific and experiential lens. Rational choice based on religious values raises the concept of rational religion choice. Their movement aims to reconstruct patriarchal domination in religion, and promote gender-inclusive religion through re-reading sacred texts with various holistic and contextual approaches to develop a new epistemology in Islam in feminism. To optimize their goals, they utilize human resources through organizations affiliated with KUPI, as well as online media to spread their ideas. The KUPI Muslim feminist movement reconstructs gender-inclusive Islam through religious rationality, organizational advocacy, and the use of digital media.